Reviving the Overlooked: Strategies for Reclaiming the Forgotten Part of Marketing - Al-Hadrawi, Baqer Khudair; Kaushik, Meenakshi; Reniati, Reniati (Universitas Bangka Belitung, 2024)
In the realm of marketing, certain facets often find themselves relegated to the periphery, overlooked and underestimated. This theoretical exploration delves into strategies for reviving these neglected elements, aiming to reclaim their significance within the broader marketing landscape. In the dynamic world of consumer behavior and evolving market trends, it becomes imperative to reassess and reinvigorate those components that have been marginalized over time. This study postulates that a theoretical foundation can catalyze innovation, offering marketers a blueprint for revitalizing overlooked aspects. By challenging conventional norms and engaging in theoretical discourse, professionals can uncover latent potential and undiscovered opportunities within their marketing arsenal. The theoretical lens allows for a comprehensive examination of the overlooked facets, dissecting the intricacies that may have led to their neglect. This process not only facilitates a deeper understanding of the dynamics at play but also sets the stage for strategic interventions. As marketing evolves, embracing a theoretical framework becomes paramount in deciphering the nuances of consumer psychology, technology integration, and societal shifts, ultimately empowering marketers to breathe new life into forgotten realms and redefine the boundaries of effective engagement.